For what value of *k* will *x* - 4 be a factor of *x*^2 + *kx* - 52? Show how you arrived at your answer.

GAMEMASTERX40 Feb 12, 2019

#1**+2 **

Remember GM....if x - 4 is a factor then 4 is a root

This is where the Remainder Theorem comes in handy

So....if 4 is a root....then putting 4 into the function will return 0....so....

(4)^2 + k(4) - 52 = 0 simplify

16 + 4k - 52 = 0

-36 + 4k = 0 add 36 to both sides

4k = 36 divide both sides by 4

k = 9

So....we have x^2 + 9x - 52

Notice that this factors as ( x - 4) (x + 13)

Note that (x - 4) is a factor

CPhill Feb 12, 2019